1994
DOI: 10.1021/bi00174a005
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Protease Inhibitors: Evaluation of Resistance Engendered by Amino Acid Substitutions in the Enzyme's Substrate Binding Site

Abstract: The human immunodeficiency virus type 1 (HIV-1) protease is a homodimeric aspartyl endopeptidase that is required for virus replication. A number of specific, active-site inhibitors for this enzyme have been described. Many of the inhibitors exhibit significant differences in activity against the HIV-1 and HIV type 2 (HIV-2) enzymes. An initial study was conducted to ascertain the HIV-1 protease's potential to lose sensitivity to several test inhibitors while retaining full enzymatic activity. The substrate bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…To date, several studies have examined the acquisition of HIV-1 resistance to protease inhibitors and have determined the changes required in the protease to reduce sensitivity to a variety of these compounds (Condra et al, 1995;Danziani et al, 1993;el-Farrash et al, 1994;Ho et al, 1994;Kaplan et al, 1994;Markowitz et al, 1995;Otto et al, 1993 ;Patick et al, 1995 ;Sardana et al, 1994). In vivo and in vitro, HIV-1 resistance to several distinct protease inhibitors is often induced by common amino acid substitutions that can confer various levels of cross-resistance (Condra et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have examined the acquisition of HIV-1 resistance to protease inhibitors and have determined the changes required in the protease to reduce sensitivity to a variety of these compounds (Condra et al, 1995;Danziani et al, 1993;el-Farrash et al, 1994;Ho et al, 1994;Kaplan et al, 1994;Markowitz et al, 1995;Otto et al, 1993 ;Patick et al, 1995 ;Sardana et al, 1994). In vivo and in vitro, HIV-1 resistance to several distinct protease inhibitors is often induced by common amino acid substitutions that can confer various levels of cross-resistance (Condra et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies indicate that cross-resistance is a major obstacle inherent to most PIs (4,16,30). This observation should not be a surprise because all the inhibitors were designed to bind wild-type enzyme.…”
mentioning
confidence: 99%
“…Modeling studies by Gustchina et al revealed that differences in the affinity of HIV-1 and HIV-2 proteases to two aspartic PI appeared to be due in part to I32V (27). Sardana and colleagues mutated the four amino acid positions in HIV-1 protease to the corresponding HIV-2 amino acids and performed enzyme activity and inhibition studies using purified proteases in the presence of three inhibitors: L-689,502, L-731,723, and RO 31-8959 (later licensed as SQV) (29). Although their results supported the findings of Gustchina et al, the authors noted that substitutions at residues 47, 76, and 82 had relatively minor effects on protease inhibition by these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In HIV-1, a substitution at any one of these residues confers multi-PI resistance (26), and common drug resistance mutations at positions 32, 47, and 82 encode the corresponding wild-type (WT) amino acids from HIV-2. Early structural and biochemical studies showed that these residues contribute to substrate selectivity (27,28), as well as inhibitor sensitivity (29), although most of these observations were made using investigational PI which were never licensed. More recently, crystallographic studies have linked three of the four residues (32, 47, and 82) to differential amprenavir (APV) and DRV sensitivities (30)(31)(32)(33).…”
mentioning
confidence: 99%